Degradation of Polypropylene Using Fungal Enzyme As A Sustainable Approach To Management Plastic Waste - Ong, Ghim Hock; Kee, Wong Kok; Ahmed, Rowan Diaaeldin Ahmed Hussein; Ying, Joelene K’ng Zi; Rui, Wong Rui; Er, Loh Khye; Tanee, Tawatchai (Malaysian Applied Biology, 2024)
Polypropylene (PP) is a major environmental problem in Malaysia because it has been ranked the 28th highest plastic polluter in the world (at 56kg per capita per year) in 2021. Landfilling is one of the most common ways of dealing with plastic because leachate may cause increased probability of cancer and neurological impairment in humans. The use of fungi in mycoremediation makes the process eco-friendly. In addition, fungi have a vast hyphal network and broader metabolic competence. The objective of this study was to investigate fungi remediation of PP via the detection of manganese peroxidase and laccase activity in Bushnell Haas Broth (BHB). PP degradation activity was measured via the activity of laccase and manganese peroxidase at a wavelength of 450nm and 610nm, respectively. Of the 17 species of fungi isolated from the Jeram landfill, 12 species of fungi showed growth in BHB with PP as the sole carbon source. Penicillium sp. 1, Aspergillus sp., Penicillium levitum, Talaromyces louisianensis, Aspergillus tamarii, Cunninghamella bertholletiae, Penicillium sp. 2 and Aspergillus niger demonstrated high and longer laccase activity, and these fungi could be considered as potential fungi. P. levitum, P. janthinellum, Penicillium sp, and T. louisianensis have high and longer MnP activity. In summary, P. levitum and T. louisianensis have a high and long duration of MnP and laccase activity in degrading PP, which can be developed and integrated into plastic waste management.